2015
DOI: 10.1371/journal.pone.0123606
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Prevalence of Disrespect and Abuse during Childbirth in Kenya

Abstract: BackgroundPoor quality of care including fear of disrespect and abuse (D&A) perpetuated by health workers influences women’s decisions to seek maternity care. Key manifestations of D&A include: physical abuse, non-consented care, non-confidential care, non-dignified care, discrimination, abandonment, and detention in facilities. This paper describes manifestations of D&A experienced in Kenya and measures their prevalence.MethodsThis paper is based on baseline data collected during a before-and-after study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
297
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 267 publications
(385 citation statements)
references
References 15 publications
44
297
30
2
Order By: Relevance
“…In this study, the proportion of women (22%) who reported D and A during labour and delivery is similar to studies conducted in Kenya and Ethiopia [12,16], although lower than that reported in a study conducted in Nigeria (98%) [17]. The commonly reported incidents of D and A in this study were similar to those reported in many from sub-Saharan African countries [13].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In this study, the proportion of women (22%) who reported D and A during labour and delivery is similar to studies conducted in Kenya and Ethiopia [12,16], although lower than that reported in a study conducted in Nigeria (98%) [17]. The commonly reported incidents of D and A in this study were similar to those reported in many from sub-Saharan African countries [13].…”
Section: Discussionsupporting
confidence: 83%
“…The proportion of women left unattended during labour (6%) was low in this study compared to that reported in other studies [12,14]. This could well be due to routine performance evaluations that were implemented in health services at the time of this study.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations